Cognitive remediation therapy plus standard care versus standard care for people with schizophrenia - Pentaraki, Alexandra (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of cognitive remediation therapy plus standard care in people with schizophrenia compared with standard care.